Bar Code Events in the Juno‐UVS Data: Signature ∼10 MeV Electron Microbursts at Jupiter. Issue 22 (21st November 2018) - Bonfond, B.; Gladstone, G. R.; Grodent, D.; Gérard, J.‐C.; Greathouse, T. K.; Hue, V.; Kammer, J. A.; Versteeg, M. H.; Davis, M. W.; Becker, H. N.; Radioti, A.; Elliott, S. S.; et al.
Abstract: One of the most intriguing discoveries of Juno is the quasi‐systematic detection of upgoing electrons above the auroral regions. Here we discuss a by‐product of the most energetic component of this population: a contamination resembling bar codes in the Juno‐UVS images. This pattern is likely caused by bursts of ∼10 MeV electrons penetrating the instrument. These events are mostly detected when Juno's magnetic footprint is located poleward of the main emission relative to the magnetic pole. The signal is not periodic, but the bursts are typically 0.1–1 s apart. They are essentially detected when Juno‐UVS is oriented toward Jupiter, indicating that the signal is due to upgoing electrons. The event detections occur between 1 and 7 Jovian radii above the 1‐bar level, suggesting that the electron acceleration takes place close to Jupiter and is thus both strong and brief. Plain Language Summary: Someone's noise is always someone else's signal. Here we use the Juno‐UVS ultraviolet spectrograph on board the Juno spacecraft as a particle detector rather than a photon collector. We analyze artifacts looking like a bar code in ultraviolet images of Jupiter's aurora to investigate a very specific kind of radiation above the poles. These bar code events are caused by very sporadic bursts of relativistic electrons arising from the aurora itself, rather than the radiation belts. This indicates the existence of a very efficient mechanism accelerating electrons upward right above Jupiter's atmosphere. Key Points: Rapidly varying noise caused by ∼10 MeV penetrating electrons creates bar code patterns in Juno‐UVS data The typical timescale is ∼0.1‐1 s The magnetic footprints of these bar code events are mostly located poleward of the main auroral emission relative to the magnetic pole